2009
DOI: 10.1039/b912513b
|View full text |Cite
|
Sign up to set email alerts
|

Vertically oriented arrays of polyaniline nanorods and their super electrochemical properties

Abstract: Highly dense arrays of ordered and aligned nanorods of polyaniline with 10 nm diameter on transparent ITO substrate have been successfully fabricated using supramolecular assemblies of block copolymer as scaffold material; the ordered arrays of polyaniline nanorods so fabricated were found to exhibit excellent electrochemical properties with an electrochemical capacitance value of 3407 F g(-1).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
122
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 209 publications
(125 citation statements)
references
References 16 publications
2
122
1
Order By: Relevance
“…A low rate of polymerization facilitates the orientation of PANI on the specic substrate to avoid the random agglomeration. [16][17][18][19][20][21][22] Based on this analysis, it can be concluded that the interface between the water and organic phases is an important chemical site for the deposition of ordered nanostructures of PANI at an extremely low rate of polymerization, which is controlled by a small amount of aniline diffusing from organic solvent to the interface. Furthermore, a stable diffusion rate of aniline at the interface might enable aniline to polymerize at a high current density.…”
Section: Introductionmentioning
confidence: 96%
“…A low rate of polymerization facilitates the orientation of PANI on the specic substrate to avoid the random agglomeration. [16][17][18][19][20][21][22] Based on this analysis, it can be concluded that the interface between the water and organic phases is an important chemical site for the deposition of ordered nanostructures of PANI at an extremely low rate of polymerization, which is controlled by a small amount of aniline diffusing from organic solvent to the interface. Furthermore, a stable diffusion rate of aniline at the interface might enable aniline to polymerize at a high current density.…”
Section: Introductionmentioning
confidence: 96%
“…8,9 Nanostructured conducting polymers have been fabricated so far using template-free synthesis, [10][11][12] soft-template synthesis using surfactants, [13][14][15] micelles, 16,17 DNA, 18,19 and hard-template synthesis using track-etched membranes, [20][21][22] anodized aluminium oxide (AAO) membranes, [23][24][25][26][27][28][29][30] and block copolymer templates. [31][32][33] In the block copolymer templating process, conducting polymer nanorods are fabricated by selective polymerization in one of the microphase-separated domains. The electropolymerization basically employs porous cylinders that are prepared by additional treatment for removal of one of the domains.…”
Section: Introductionmentioning
confidence: 99%
“…31 Kuila and Stamm reported the fabrication of a conduct-ing polyaniline nanorod array by electropolymerization using a porous poly(styrene-b-4-vinylpyridine) (PS-b-P4VP) thin film. 32,33 The nanorods were 10 nm in diameter with a 25 nm periodicity. 32, 33 32, 33 32, 33 32, 33 In the chemical polymerization procedure, an amphiphilic diblock copolymer thin film without etching of one of the domains is generally used as a template.…”
Section: Introductionmentioning
confidence: 99%
“…In the typical application of block copolymers as thin films, the structural behavior could be more complicated compared to the bulk, due to their interactions with the underlying substrate. This class of ordered materials is applicable to the fields of, e.g., lithography, surface patterning, semiconducting nanomaterials and biosensing devices [8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%